ANALYSIS OF THE OMNIBUS LAW ON JOB CREATION IN THE PERSPECTIVE OF SOCIOLOGY OF LAW - Mohammad Dimas Atmadja; Titi Yuliati; Upik Mutiara (Universitas Muhammadiyah Tangerang, 2020)
One of the widely discussed issues is related to the implementation of the Omnibus Law on Job Creation. In the Omnibus Law, there are 3 patterns, namely